Estudio de prefactibilidad para la instalación de una planta industrial de hojuelas de mashua deshidratada - Mesa La Rosa, Fiorella Gianina (2020)
Dehydrated mashua flakes is an innovative product because it uses the convective dehydration method. It is characterized by a little spicy taste and contain nutritional benefits for the body of people, thus reducing the risks of diseases such as anemia, diabetes, kidney symptoms, prostate and cancer. With the purpose of promoting the industrialization of national products such as mashua; specifically, access to more profitable markets niches is born the proposal of the present research work, our general objective is to determine the feasibility in the installation of a plant producing dehydrated flakes of mashua from its financial, technological, social and economic viability. The plant will be located in the department of Lima, in the province of Huaral, because it offers a low cost per m2 of land for the installation of the production plant. The product to study aims to enter the market of Metropolitan Lima, having as target audience the male and female population from 15 years of age to 30 years belonging to the socioeconomic level A, B and C of Metropolitan Lima. Also, the indirect distribution channel will be used, through biomarkets and supermarkets. The demand for the project for the first year is 886 278 packages of dehydrated mashua flakes of 76gr, increasing this amount annually because it seeks to have greater market share. At the beginning, it will have a 2.50% share with respect to the Peruvian market of healthy snacks. The introductory price will be S /. 4.6 per package of flakes and several marketing strategies are carried out promoting advertising campaigns to achieve customer loyalty and acceptance. A total investment of S /. 2 280 015.35 for a 5-year project and the results of the economic evaluation and financial evaluation affected the viability of the project since the indicators affected VANE and VANF are S /. 3 741 063.45 and S /. 3 806 286.61 respectively. Additional return rates TIRE 54.54% and TIRF 81.34% are higher than COK (10.8%) and the investment recovers at most in 3 years.